Renal transplant from infant and neonatal donors is a feasible option for the treatment of end‐stage renal disease but is associated with increased early graft loss. Issue 11 (13th August 2018) - Wijetunga, Imeshi; Ecuyer, Clare; Martinez‐Lopez, Sonsoles; Jameel, Muhammad; Baker, Richard J.; Welberry Smith, Matthew; Patel, Chirag; Weston, Michael; Ahmad, Niaz
Abstract : Kidney transplants from young pediatric donors are uncommonly performed in the UK. Published literature of kidney transplant from donors weighing less than 5 kg is sparse. We present our initial experience of en bloc kidney transplantation (EKT) from donors weighing less than 20 kg, including neonatal donors. All recipients undergoing EKT from donors under 20 kg at our center from January 2005 to October 2016 were included. Donor and recipient details were recorded from a prospective database. Electronic patient records were examined for follow‐up data. Of 30 EKTs included, 15 were from ≤5 kg donors and 15 from >5 kg donors (median weight 3.4 and 12.7 kg, respectively). One‐year graft survival for ≤5 kg and >5 kg donors for EKT was 86.7% and 93.3% ( P  = 0.85), respectively. Progressive improvement in estimated GFR (eGFR) was noted in both donor categories through first‐year posttransplant but in the ≤5 kg donor category significant improvement was seen at 12 months compared to 3 months after transplantation (median eGFR 37.3 vs 70.0 mL/min/1.73 m 2, P  = 0.03). Two early graft losses were attributable to early vascular complications and one graft loss due to primary nonfunction. Our data show that kidney transplantation from such donors is a feasible option at centers with experience of EKT, albeit with increased risk of early graft loss. Abstract : The authors report a United Kingdom single‐center experience of en bloc kidney transplantation from infant and neonatal donors, which demonstrates acceptable short‐term graft and patient outcomes despite an increased risk of early graft loss.